1986
DOI: 10.1177/00220345860650021201
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Teeth Restored with Class II Bonded Composite Resin

Abstract: The purpose of this study was to determine whether composite resin bonded to enamel or to both enamel and dentin can increase the fracture resistance of teeth with Class II cavity preparations. Extracted maxillary pre-molars with MOD slot preparations were restored with composite resin bonded to enamel (P-30 and Enamel Bond) or composite resin bonded to enamel and dentin (P-30 and Scotch-bond). Teeth in a control group were prepared but left unrestored. All teeth were loaded occlusally in a universal testing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
20

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 14 publications
2
65
0
20
Order By: Relevance
“…This means that the reinforcing effect of resin composite may be diminished under clinical conditions. 22 In group 6, significant differences were observed compared to groups 1, 3, 4 and 5 and insignificant differences were noted compared with group 2 (p>0.05). For this reason, it could be suggested that, if, during cavity preparation in endodontically-treated maxillary premolars, the remaining marginal ridge was 0.5 mm, it should be retained.…”
Section: Troppe and Tronstadmentioning
confidence: 75%
See 1 more Smart Citation
“…This means that the reinforcing effect of resin composite may be diminished under clinical conditions. 22 In group 6, significant differences were observed compared to groups 1, 3, 4 and 5 and insignificant differences were noted compared with group 2 (p>0.05). For this reason, it could be suggested that, if, during cavity preparation in endodontically-treated maxillary premolars, the remaining marginal ridge was 0.5 mm, it should be retained.…”
Section: Troppe and Tronstadmentioning
confidence: 75%
“…26 On the other hand, in the mouth, repeated loading could lead to fatigue failure, 22 consequently, interpretation of the results should be done cautiously.…”
Section: Troppe and Tronstadmentioning
confidence: 99%
“…Previous studies have shown the diffi culty of obtaining uniform fracture strengths for human teeth because of natural variations in tooth morphology 13,14) . Emulating the experimental protocols of Karapinar Kazandag et al 5) and Ulusoy et al 10) , optimum care was taken in this study to standardize the experimental teeth according to their tooth sizes and dimensions and working length measurements.…”
Section: Standardization Of Experimental Teeth and Experimental Methomentioning
confidence: 99%
“…Adhesive restoration for endodontically treated teeth offers many advantages over the use of traditional, nonadhesive materials. For instance bonded resins permit transmission of functional stresses across the bonded interface to the tooth, with the potential to reinforce weakened tooth structure 24) . Using adhesive materials properly can reduce microleakage of interface between these materials and tooth structure.…”
Section: 국문초록mentioning
confidence: 99%